Recommendations for intervertebral disc notochordal cell investigation: From isolation to characterization - Rebecca J. Williams; Lisanne T. Laagland; Frances C. Bach; Lizzy Ward; Wilson Chan; Vivian Tam; Adel Medzikovic; Shaghayegh Basatvat; Lily Paillat; Nicolas Vedrenne; Joseph W. Snuggs; Deepani W. Poramba‐Liyanage; et al. (JOR Spine, 2023)
Abstract Background Lineage‐tracing experiments have established that the central region of the mature intervertebral disc, the nucleus pulposus (NP), develops from the embryonic structure called “the notochord”. However, changes in the cells derived from the notochord which form the NP (i.e., notochordal cells [NCs]), in terms of their phenotype and functional identity from early developmental stages to skeletal maturation are less understood. These key issues require further investigation to better comprehend the role of NCs in homeostasis and degeneration as well as their potential for regeneration. Progress in utilizing NCs is currently hampered due to poor consistency and lack of consensus methodology for in vitro NC extraction, manipulation, and characterization. Methods Here, an international group has come together to provide key recommendations and methodologies for NC isolation within key species, numeration, in vitro manipulation and culture, and characterization. Results Recommeded protocols are provided for isolation and culture of NCs. Experimental testing provided recommended methodology for numeration of NCs. The issues of cryopreservation are demonstrated, and a pannel of immunohistochemical markers are provided to inform NC characterization. Conclusions Together we hope this article provides a road map for in vitro studies of NCs to support advances in research into NC physiology and their potential in regenerative therapies.